1987
DOI: 10.1002/pola.1987.080250826
|View full text |Cite
|
Sign up to set email alerts
|

FT–IR spectroscopic study on the photo‐ and photooxidative degradation of nylons

Abstract: SynopsisThe progress of photo-and photooxidative degradation of nylon films were studied by FT-IR spectroscopy. The gases evolved from the photolysis of various nylons and their model amides were also analyzed. The formation of double bonds, changes of crystallinity, and the effect of amino and carboxyl end groups has been studied and discussed. The band shapes of the IR spectra pertaining to the carbonyl groups formed by thermal oxidation or photooxidation were found to be very similar, suggesting that the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Do et al (12,13) did Fourier transform IR studies on photooxidative and thermal oxidative degradation of nylon. They found a decrease in amide and methylene bands and an increase of carbonyl groups upon nylon; where the carbonyl groups were of many origins, such as aldehydes, carboxylic acids, ketones, N-acylamides and α, β-unsaturated carbonyl compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Do et al (12,13) did Fourier transform IR studies on photooxidative and thermal oxidative degradation of nylon. They found a decrease in amide and methylene bands and an increase of carbonyl groups upon nylon; where the carbonyl groups were of many origins, such as aldehydes, carboxylic acids, ketones, N-acylamides and α, β-unsaturated carbonyl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Coconut oil was purchased from Sigma Chemical Co. (St. Louis, MO) and spermaceti wax from Sargent Welch (Skokie, IL). Radioisotope-labeled [4,8,12,13,17, H]-squalene was obtained from New England Nuclear Products (Boston, MA). An 8% (wt/vol) squalene solution was made with toluene; for radiotracer analysis, an aliquot of 200 µL of 0.01 mCi/mL 3 H-labeled squalene was added to 20 mL of the soiling solution.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Instead, if the available data are sufficiently diagnostic, then one is in a position to test different theories and to discriminate among them (theory testing), as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity changes also show that the postheated samples exhibit a higher level of UVabsorbing fluorescent and phosphorescent species at 294 nm. The shapes of the carbonyl envelope [45] of the infrared (IR) spectrum formed in thermal and photooxidation were similar, suggesting that both the oxidation mechanisms are the same. The broadness of these bands indicated that the carbonyl group spectra arise from more than one species.…”
Section: Degradation Of Nylon 66mentioning
confidence: 91%